Biodegradation of carbamazepine using freshwater microalgae Chlamydomonas mexicana and Scenedesmus obliquus and the determination of its metabolic fate. (April 2016) - Xiong, Jiu-Qiang; Kurade, Mayur B.; Abou-Shanab, Reda A.I.; Ji, Min-Kyu; Choi, Jaeyoung; Kim, Jong Oh; Jeon, Byong-Hun
Highlights: Toxicological effects of carbamazepine on C. mexicana and S. obliquus was studied. C. mexicana was tolerant to carbamazepine, and could withstand at its high dose. Carbamazepine influenced the biochemical characteristics of microalgal cells. SOD and CAT activity was increased in algae under toxic stress of carbamazepine. Microalgal strains showed simultaneous bioaccumulation and biodegradation of CBZ. Abstract: This study evaluated the toxicity and cellular stresses of carbamazepine (CBZ) on Chlamydomonas mexicana and Scenedesmus obliquus, and its biodegradation by both microalgal species. The growth of both microalgal species decreased with increase of CBZ concentration. The growth of S. obliquus was significantly inhibited (97%) at 200 mg CBZ L −1, as compared to the control after 10 days; whereas, C. mexicana showed 30% inhibition at the same experimental conditions. Biochemical characteristics including total chlorophyll, carotenoid contents and enzyme activities (SOD and CAT) for both species were affected by CBZ at relatively high concentration. C. mexicana and S. obliquus could achieve a maximum of 35% and 28% biodegradation of CBZ, respectively. Two metabolites (10, 11-dihydro-10, 11-expoxycarbamazepine and n -hydroxy-CBZ) were identified by UPLC-MS, as a result of CBZ biodegradation by C. mexicana . This study demonstrated that C. mexicana was more tolerant to CBZ and could be used for treatment of CBZ contaminated wastewater.